Efficacy and safety of the integration of traditional Chinese medicine and western medicine in the treatment of diabetes-associated cognitive decline: a systematic review and meta-analysis - Su, Jianan; Sun, Guiyan; An, Jiren; Ao, Yuhan; Li, Jing; Shen, Zihan; Zhang, Lanyi; Zhang, Shiheng; Yang, Yufeng; Shi, Yan (Frontiers in Pharmacology, 2023)
Objective. In order to offer possible therapeutic treatment evidence for diabetes-associated cognitive decline (DACD), we thoroughly evaluated the effectiveness and safety of combining Traditional Chinese Medicine (TCM) and Western Medicine (WM) in the current study. Methods. The present study employed a comprehensive search strategy across multiple databases, namely PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chinese Scientific Journals Database (VIP), and Chinese Biomedical Literature Database (CBM), to identify relevant articles published until July 2023. Subsequently, a systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted to assess the efficacy and safety of integrating TCM with WM for the treatment of DACD. The literature included in this study was assessed using the GRADE criteria and the Cochrane Handbook for Systematic Reviews of Interventions. Statistical analysis was conducted using RevMan 5.4 software. Results. A total of 20 RCTs involving 1570 patients were ultimately included in this meta-analysis. The pooled results demonstrated that the integration of TCM and WM therapy significantly enhanced the overall effectiveness rate compared to WM therapy alone . Additionally, the combination therapy resulted in reductions in fasting blood glucose , HbA1c, TNF-α levels, and TCM Syndrome Score . Meanwhile, the combination therapy had a positive effect on MoCA Score , and MMSE Score. In addition, the safety of the combination therapy was comparable to that of the WM alone. Conclusion. The integration of TCM and WM therapy outperformed WM alone in DACD treatment. Simultaneously, the combination therapy could improve the therapeutic effect on blood glucose, cognitive function, and inflammation to a certain extent with few adverse effects. However, given the constraints imposed by the quality limitations of the incorporated studies, as well as the potential presence of reporting bias, it is imperative that our findings be substantiated through rigorous, largescale, randomized controlled trials of superior quality in the future.